EVALUATION OF THE BIOLOGICAL CONTROL EFFICIENCY OF FOUR SPIDERS USING FUNCTIONAL RESPONSE EXPERIMENTS - KHAN, AKHTAR ALI (The Bioscan, 2013)
The biological control efficiency of four spiders, Pardosa altitudis Tikader and Malhotra (Lycosidae), Leucage celebesiana Walckenaer (Teragnathiade), Neoscona rumpfi Tikader and Bal (Araneidae), Theridion manjithar Tikader (Theridiidae) preying on different densities of cabbage aphid, Brevicoryne brassicae (L.) (Homoptera: Aphididae) was evaluated using functional response experiments. The results revealed that all four spiders exhibited a decelerating curve, typical of type II functional response, on different densities of prey as determined by a non-linear logistic regression model. The maximum prey consumption per day at highest density of cabbage aphids were 54.2 for P. altitudis, 48.9 for N. rumpfi, 41.2 for L. celebesiana, and 37.3 for T. manjithar. The estimate of search rate was maximum for L. celebesiana (3.24104 h-1) while minimum handling time was noted for P. altitudis (0.38914 h). In most of the treatments, the estimates of search rates did not show significant differences, while the handling times mostly showed significant variations among the spider species. The P. altitudis exhibited lowest handling time with high search rate followed by N. rumpfi. Hence, P. altitudis has the efficiency to be exploited successfully as a biocontrol agent for the management the cabbage aphid populations in cruciferous vegetable ecosystem.